Practical guidelines for device characterization and power converter design involving SiC MOSFETs - Yeo, Howe Li (2020)
SiC MOSFETs offer significant advantages over Si IGBTs in terms of power density and efficiency for power converter design. However, their fast switching speeds and limited short circuit current capability lead to issues during device characterization and converter design. In this paper, guidelines for overcoming the practical issues of characterizing and designing with SiC MOSFETs are presented. A double pulse test setup and a SiC-based dual-active bridge are developed by incorporating the guidelines. Experimental results are obtained where applicable to illustrate the benefits of these guidelines.